Epidemiological aspects of cervical câncer cases in Brazil from 2016 to 2021 (Research, Society and Development, 2022)
Objective: To characterize the epidemiological situation of cervical cancer cases in Brazil from 2016 to 2021, in order to analyze the diagnostic notifications of precursor lesions and deaths. Methods: This is a descriptive observational epidemiological study with a quantitative approach through secondary data from health information obtained from the SUS Hospital Information System database (SIH/SUS) and the Cancer Information System (SISCAN). Results/Discussion: between 2016 and 2021, there were 28,789 reported cases of neoplasms in patients aged 15 to 29 years in Brazil. When analyzing the profile of individuals with cervical cancer, it was found that most have CIN I and are aged between 25-29 years. Regarding deaths, the most prevalent age group was 25-29 years old, in brown women and in the Southeast region. In Sergipe, the highest incidence range was 25-29 years. Conclusion: the analyzed data collaborate to understand the epidemiology of cervical cancer in Brazil, in addition to directing health promotion, prevention and rehabilitation actions. Finally, it is extremely important that there are new epidemiological studies, especially in regions with the highest incidence and in regions with little documented data.